A Meta‐Analysis of Pulmonary Function With Pulsatile Perfusion in Cardiac Surgery. Issue 2 (2nd May 2014) - Lim, Choon‐Hak; Nam, Myung‐Ji; Lee, Ji‐Sung; Kim, Hyun‐Jung; Kim, Ji‐Yeon; Shin, Hye‐Won; Lee, Hye‐Won; Sun, Kyung
Abstract The aim of this study was to determine whether pulsatile or nonpulsatile perfusion had a greater effect on pulmonary dysfunction in randomized controlled trials. MEDLINE, EMBASE, and the Cochrane Central Register of Controlled Trials were used to identify available articles published before April 13, 2013. A meta‐analysis was conducted on the effects of pulsatile perfusion on postoperative pulmonary function, intubation time, and the lengths of intensive care unit (ICU) and hospital stays. Eight studies involving 474 patients who received pulsatile perfusion and 496 patients who received nonpulsatile perfusion during cardiopulmonary bypass (CPB) were considered in the meta‐analysis. Patients receiving pulsatile perfusion had a significantly greater PaO2/FiO2 ratio 24 h and 48 h post‐operation (P < 0.00001, both) and significantly lower chest radiograph scores at 24 h and 48 h post‐operation (P < 0.00001 and P = 0.001, respectively) compared with patients receiving nonpulsatile perfusion. The incidence of noninvasive ventilation for acute respiratory insufficiency was significantly lower (P < 0.00001), and intubation time and ICU and hospital stays were shorter (P = 0.004, P < 0.00001, and P < 0.00001, respectively) in patients receiving pulsatile perfusion during CPB compared with patients receiving nonpulsatile perfusion. In conclusion, our meta‐analysis suggests that the use of pulsatile flow during CPB results in better postoperative pulmonary function and shorter ICU and hospital stays.